1993
DOI: 10.1093/oxfordjournals.humrep.a137926
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation diagnosis: Sephadex filtration and human serum albumin gradients do not select spermatozoa by sex chromosome: a fluorescent in-situ hybridization study

Abstract: Fluorescent in-situ hybridization (FISH) of decondensed sperm nuclei has been used directly to evaluate the enrichment efficiency of human sperm separation using Sephadex gel filtration and human serum albumin (HSA) gradients. Control and processed spermatozoa were fixed and their nuclei decondensed. In-situ hybridization was carried out with a Y-specific DNA probe (DYZ1). Sephadex filtration yielded 52.5% Y-chromosome-bearing spermatozoa, HSA separation resulted in 49.4% Y-chromosome-bearing spermatozoa and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…To obtain sperm nuclei, an aliquot of frozen spermatozoa was thawed and washed in NaCl 0.9% to eliminate cryoprotectant. The sample was fixed and decondensed following Vidal et al 15 Slides were maintained at 7208C until hybridisation.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain sperm nuclei, an aliquot of frozen spermatozoa was thawed and washed in NaCl 0.9% to eliminate cryoprotectant. The sample was fixed and decondensed following Vidal et al 15 Slides were maintained at 7208C until hybridisation.…”
Section: Methodsmentioning
confidence: 99%
“…By using molecular techniques, mainly fluorescence in situ hybridization (FISH), it was demonstrated that albumin gradients [10,11], Sephadex columns [10,12,13] and swim-up [13,14] techniques do not significantly alter the Y-to X-bearing spermatozoa ratio. But the discontinuous Percoll gradients technique was reported to be the only method to alter the X-and Y-bearing sperm ratio [15,16].…”
mentioning
confidence: 99%
“…Sperm nuclear decondensation was performed according to the method described by Vidal et al 20 In brief, the slides were exposed to 5 mmol l 21 dithiothreitol plus 0.1 mol l 21 Tris/1% (v/v) Triton-X for at least 12 min at 37 uC, and then immediately transferred to 23strength saline-sodium citrate buffer for 3 min at room temperature, and dehydrated in an ethanol series of 70%, 90% and 100% for 2 min each. The slides were then air-dried at room temperature.…”
Section: Methods Of Sperm Selectionmentioning
confidence: 99%